Release of apoptosis inhibitor of macrophage (AIM) from pentameric IgM in serum predicts prognosis after hemodialysis initiation - Keisuke Yasuda; Akemi Nishijima; Tomoko Inoue; Toshio Takagi; Kazunari Tanabe; Jun Minakuchi; Satoko Arai; Toru Miyazaki (Communications Medicine)
Abstract Background The optimal timing for initiating dialysis and prognostic markers in chronic kidney disease (CKD) patients are under debate, with mortality and cardiovascular risks varying among patients. This study investigates whether the apoptosis inhibitor of macrophage (AIM), which is mostly bound to pentameric IgM, could serve as an effective indicator. Methods We prospectively followed 423 patients at dialysis initiation and 563 at various CKD stages. AIM dissociation from IgM and other serum components were measured in their serum samples. In vitro treatment of IgM-AIM complexes with their serum was conducted to assess AIM release from IgM. Survival analysis determined the associations of each variable with mortality and cardiovascular risk, and a cutoff value was calculated and validated using cross-validation. Results AIM dissociation from IgM increases with CKD progression and correlates with the serum uremic state, as shown by enhanced AIM release from IgM in vitro with sera from patients starting dialysis, but not those at earlier CKD stages. Patients at dialysis initiation with high proportion of serum IgM-free AIM (fAIM%) show elevated uremic toxins and other toxic metabolites, higher mortality, and increased cardiovascular risk compared to those with low fAIM%. This prognostic association is not seen with other CKD biomarkers, such as eGFR, creatinine, or inositol-phosphate. We determined the fAIM% cutoff of 46.27%, which predicts mortality two years post-dialysis initiation. Conclusions These findings suggest that the serum fAIM% could function as a prognostic marker at dialysis initiation and may have potential as a criterion for determining dialysis timing.